Analysis of Environmental Risk Factors for Leptospirosis in Bantul, Yogyakarta, Indonesia - Andri Setiawan; Noor Alis Setiyadi; Bhisma Murti (Masters Program in Public Health, 2024)
Background: Leptospirosis is a disease caused by the bacterium leptospira sp. The number of cases and deaths due to leptopirosis from year to year is always increasing. The purpose of this study is to analyze environmental risk factors for the incidence of leptospirosis in Bantul Regency, Special Region of Yogyakarta, Indonesia.Subjects and Method: This study uses an observational analytical approach with a cross-sectional design. The research location is in Bantul Regency with a sample of 200 research subjects. The sampling technique is fixed disease sampling. The dependent variable was the incidence of leptospirosis and the independent variables were the physical condition of the house, the condition of the residential environment, the presence of rats, the presence of livestock or pets, near rivers, flooded areas, occupation, habits of using personal protective equipment, age and gender. The research instruments used were questionnaires and checklists and the data was analyzed using logistic regression analysis.Results: Risk factors that increase the incidence of leptospirosis are poor home conditions (OR= 2.18; 95% CI = 1.12 to 4.24; p=0.022); Poor residential environmental conditions (OR = 2.58; 95% CI = 1.33 to 5.03; p = 0.005); presence of rats inside and/or outside the home (OR = 4.51; 95% CI = 1.40 to 14.55; p = 0.012). The risk of leptospirosis infection decreases with the use of PPE (OR = 0.17; 95% CI= 0.08 to 0.37; p<0.001).Conclusion: Poor house conditions, poor residential environmental conditions, the presence of rats inside and or outside the house are risk factors that increase the incidence of leptospirosis. Meanwhile, the use of PPE reduces the risk of leptospirosis infection